Предмет: Алгебра,
автор: lizarudyak210
Обчислити f(3) ,якщо f(x)= x2 + 2x -1
Ответы
Автор ответа:
3
у(х)=х²+2х-1.
у(3)=3²+2*3-1=9+6-1=14.
Ответ: 14.
wruwewir:
помогите пожалуйста с последними заданиями в профиле
Автор ответа:
0
Обчислити f(3) ,якщо f(x)= x^2 + 2x -1.
f(3)= (3)^2 + 2×3 -1=14.
2 спосіб.
f(x)= x^2 + 2x -1=(х^2+2х+1)-2=
(х+1)^2 -2;
f(3)=(3+1)^2 -2=16-2=14
Похожие вопросы
Предмет: Қазақ тiлi,
автор: damirdamir1237
Предмет: Английский язык,
автор: kovalchukmatvey9
Предмет: Геометрия,
автор: lindaminoru
Предмет: Английский язык,
автор: bettergod99
Предмет: Алгебра,
автор: winnigus